EPR quantification of vascular nitric oxide production in genetically modified mouse models. - Khoo, J; Alp, N; Bendall, J; Kawashima, S; Yokoyama, M; Zhang, Y; Casadei, B; Channon, K (2004)
With increasing use of genetically modified mice to study endothelial nitric oxide (NO) biology, methods for reliable quantification of vascular NO production by mouse tissues are crucial. We describe a technique based on electron paramagnetic resonance (EPR) spectroscopy, using colloid iron (II) diethyldithiocarbamate [Fe(DETC)2], to trap NO. A signal was seen from C57BL/6 mice aortas incubated with Fe(DETC)2, that increased 4.7-fold on stimulation with calcium ionophore A23187 [3.45+/-0.13 vs 0.73+/-0.13au (arbitrary units)]. The signal increased linearly with incubation time (r(2) = 0.93), but was abolished by addition of N(G)-nitro-l-arginine methyl ester (L-NAME) or endothelial removal. Stimulated aortas from eNOS knockout mice had virtually undetectable signals (0.14+/-0.06 vs 3.17+/-0.21 au in littermate controls). However, the signal was doubled from mice with transgenic eNOS overexpression (7.17+/-0.76 vs 3.37+/-0.43 au in littermate controls). We conclude that EPR is a useful tool for direct NO quantification in mouse vessels.